PENGEMBANGAN MODEL LATIHAN PENCAK SILAT JURUS REGU BAKU DI EKSTRAKURIKULER PSHT CABANG BLITAR - Evi Meisaroh; Supriyadi Supriyadi; Kurniati Rahayuni (Jurnal Sport Science, 2015)
Abstract: This study aimed at developing a model of training for standard grouped style of martial arts in PSHT branch Blitar for extracurricular activity. The developed model was expected to vary the existed models and to help students master the standard group style. The quantitative and qualitative data analyses were employed in percentage. The result of the small group tryout was 86% and of the big group was 87%. The developed model of training for standard grouped style of martial arts could become one of the alternatives for martial arts training.Key words: models of training, standard grouped style, martial arts.Abstrak: Penelitian ini bertujuan untuk mengembangkan model latihan pencak silat jurus regu baku di ekstrakurikuler PSHT Cabang Blitar agar lebih bervariasi sehingga dengan adanya model latihan jurus regu baku ini dapat membantu dan mempermudah siswa menguasai jurus regu baku. Teknik analisis yang digunakan adalah kuantitatif dan kualitatif berupa persentase. Dari hasil uji coba kelompok kecil adalah 86% dan hasil uji kelompok besar 87%. Dari hasil tersebut diharapkan pengembang model latihan pencak silat jurus regu baku ini bisa dijadikan alternatif latihan pencak silat.Kata kunci: model latihan, jurus regu baku, pencak silat.